(Pretty) Lady First: Effects of Mate-Related Motives on the Item-Selection Orders of Faces With Varying Attractiveness. (18th March 2019) - Zhang, Yuchi; Li, Xinyu; Li, Ping; Jia, Xiaoyu; Li, Weijian
Evolutionary theories suggest that fundamental mating-related motives might exert specific effects on human cognition and behaviors. Based on the evolutionary perspective, our prior research illustrated that the activation of mating-related motives leads to a study-time allocation bias toward highly attractive female faces. While study-time allocation is one of the aspects of the self-regulated learning process, it is unclear whether mating motives affect study decision behaviors (as measured by item-selection orders) during the learning process. Therefore, the present study followed the logic of previous research and aimed to examine the effects of mating-related motives on item-selection orders for face–name associations among faces with varying attractiveness. In two experiments, after an imagery procedure, participants in mating-related priming conditions (Experiment 1: mate search, Experiment 2: mate guarding) or control conditions performed an item-selection task. Participants were shown 16 female faces with varying attractiveness on a computer screen and were instructed to decide the order for studying the faces and corresponding names. Experiment 1 showed that activating mate-search motives led male participants to prioritize the choice of highly attractive rather than less attractive faces for studying. In Experiment 2, compared to the participants in the control condition, female participants in the mate-guarding priming condition were more likely to prioritize the choice of highly attractive rather than less attractive faces for studying. The present findings clarify that mating-related motives affect the item-selection prioritization of faces with varying attractiveness.